No effects of sweet taste exposure at breakfast for 3 weeks on pleasantness, desire for, sweetness or intake of other sweet foods: a randomised controlled trial. Issue 9 (14th May 2022) - Appleton, Katherine M.; Rajska, Jessica; Warwick, Sarah M.; Rogers, Peter J.
Abstract: This work investigated the effects of repeated sweet taste exposure at breakfast on perceptions and intakes of other sweet foods, while also examining the effects due to duration of exposure (1/3 weeks), test context (breakfast/lunch) and associations between taste perceptions and intakes. Using a randomised controlled parallel-group design, participants ( n 54, 18 male, mean age: 23·9 (sd 5·8) years, mean BMI: 23·6 (sd 3·5) kg/m 2 ) were randomised to consume either a sweet breakfast (cereal with sucralose) ( n 27) or an equienergetic non-sweet breakfast (plain cereal) ( n 27) for 3 weeks. On days 0 (baseline), 7 and 21, pleasantness, desire to eat and sweetness were rated for other sweet and non-sweet foods and sweet food consumption was assessed in an ad libitum meal at breakfast and lunch. Using intention-to-treat analyses, no statistically significant effects of exposure were found at breakfast (largest F 2, 104 = 1·84, P = 0·17, ηp 2 = 0·03) or lunch (largest F 1, 52 = 1·22, P = 0·27, ηp 2 = 0·02), and using Bayesian analyses, the evidence for an absence of effect in all rating measures was strong to very strong (smallest BF01 = 297·97 (BF01 error = 2·68 %)). Associations between ratings of pleasantness, desire to eat and intake were found (smallest r = 0·137, P < 0·01). Effects over time regardless of exposure were also found: sugars and percentage energy consumed from sweet foods increased throughout the study (smallest ( F 2, 104 = 4·54, P = 0·01, ηp 2 = 0·08). These findings demonstrate no effects of sweet taste exposure at breakfast for 1 or 3 weeks on pleasantness, desire for, sweetness or intakes of other sweet foods in either the same (breakfast) or in a different (lunch) meal context.